Analisis Penggunaan Teknologi Blockchain Dalam Pengelolaan Keamanan Data Pada Big Data - Dian Farindah Damanik; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
The integration of Big Data with Blockchain technology has become an intriguing subject of research in efforts to enhance security, efficiency, and transparency in managing data on a large scale. This article considers the potential applications of Blockchain technology in improving data security in Big Data, highlighting its benefits, challenges, and future prospects. The analysis includes strengthening data security through reliability, integrity, and immutable audit trails, as well as challenges such as scalability issues and regulatory compliance. Meanwhile, innovative and collaborative efforts from the industry contribute to a better understanding of the future integration of Blockchain with Big Data. With a focus on innovation, collaboration, and solutions to challenges, this article presents a comprehensive view of the opportunities and obstacles involved in ushering in a new era of secure and efficient data management through the integration of Blockchain with Big Data.